Norms and T-scores for screeners of alcohol use, depression and anxiety in the population of Suriname - de Beurs, Edwin; Jadnanansing, Raj; Etwaroo, Kajal; Blankers, Matthijs; Bipat, Robbert; Peen, Jaap; Dekker, Jack (Frontiers in Psychiatry, 2023)
Background There is a considerable gap between care provision and the demand for care for common mental disorders in low-and-middle-income countries. Screening for these disorders, e.g., in primary care, will help to close this gap. However, appropriate norms and threshold values for screeners of common mental disorders are lacking. Methods In a survey study, we gathered data on frequently used screeners for alcohol use disorders, (AUDIT), depression, (CES-D), and anxiety disorders (GAD-7, ACQ, and BSQ) in a representative sample from Suriname, a non-Latin American Caribbean country. A stratified sampling method was used by random selection of 2,863 respondents from 5 rural and 12 urban resorts. We established descriptive statistics of all scale scores and investigated unidimensionality. Furthermore, we compared scores by gender, age-group, and education level with t-test and Mann–Whitney U tests, using a significance level of p < 0.05. Results Norms and crosswalk tables were established for the conversion of raw scores into a common metric: T-scores. Furthermore, recommended cut-off values on the T-score metric for severity levels were compared with international cut-off values for raw scores on these screeners. Discussion The appropriateness of these cut-offs and the value of converting raw scores into T-scores are discussed. Cut-off values help with screening and early detection of those who are likely to have a common mental health disorder and may require treatment. Conversion of raw scores to a common metric in this study facilitates the interpretation of questionnaire results for clinicians and can improve health care provision through measurement-based care.